Contribution of EQA to improve Preanalytical practices by systematic verification of Laboratory Services - Cardoso, Ana (2020)
International literature describes the preanalytical phase as the most susceptible to errors due to the numerous non automated activities it involves Most EQA organizers offer preanalytical schemes to participants. There are basically three types of surveys procedures registration, samples circulation and errors registration The Portuguese EQA Programme ( provides these type of schemes for 13 years, using as a guide the ISO 15189 2012 In order to improve the evaluation of the preanalytical phase, PNAEQ recently launched two other preanalytical EQA schemes, mystery client and presential audits in 2015 and 2016 respectively. The aim of the mystery client survey is to verify whether the information provided to the patient is constant regardless the day and time or if it is dependent on the collaborator. The aim of the presential audit survey is to give the participants a tool to verify if the procedures performed daily are in accordance with laboratorial good practices recommendations. Conclusions:  Results from Mystery Client surveys demonstrate the need for written procedures and harmonization of practices for all collaborators, as more than a third of the responses differed in date/time and operator in a global view. In the Presential Audit surveys we highlight as critical points the results regarding questions 3 5 and 6 as they point to specific problems that occurred during the blood collection procedure, such as operator and patient safety, as well as the quality of the sample collected, suggesting the need to review legal and normative issues and to train collaborators. Participants who use systematically these two methodologies are monitoring some of the requirements of ISO 15189:2012, namely 4. 1.2.6, 4.3, 4.4.1, 4.14, 5.4.2 (both), 5.4.4.2 (mystery client) and 5.1.2, 5.2.2, 5.2.5, 5.3.2.5, 5.3.2.7, 5.4.4 (presential audit), contributing to release reliable results for medical decisions. For the future, we will extend the questions and items in evaluation in these two surveys to Microbiology area and continuing to offer training in Preanalytical matters.